Ethics Education for Contemporary Clinical Pharmacy Practice in Nigeria: Shortfalls and Needs - Okoro, Roland N. (Bangladesh Journal of Bioethics, 2019)
The past decade has witnessed a shift in the ambitions of pharmacists away from the core role of dispensing medicines towards more interesting and rewarding relationships and responsibilities with other healthcare providers and patients. The patient-centred role of pharmacists has allowed ethical issues experienced in medical practice to surface in pharmacy practice, resulting in an increase in the number and variety of ethical dilemmas that pharmacists face in their routine pharmacy practice. Pharmacy education prepares pharmacy students for practice and must be in tune with the professional dynamics. Many countries that provide patient-centered pharmacy services have redesigned pharmacy ethics education while others are in various stages of revision of their curriculum in order to adequately equip future pharmacists with the rudiments required to handle ethical issues in clinical pharmacy practice. In contrast, in Nigeria, little or no pharmacy ethics is taught to pharmacy students and the challenge lies with the curriculum design and method of teaching.